Increasing Student’s Cognitive through Problem Based Learning - Riris Sejati Adjiningsih; Ani Sulistyarsi; Juli Sukimarwati (Bioedukasi: Jurnal Pendidikan Biologi, 2023)
Based on the observation in the class of X F at SMAN 6 Madiun, it showed that students lack of curiosity, low desire in asking and expressing opinions, and lower enthusiasm for reading sources of information. Through the classroom action, this study aim to increase students’ cognitive on biotechnology with problem based learning (PBL) model. This research was conducted with three cycles. The cycle consists of four stages such as planning, action implementation, observation, and reflection. The target of study amounted to 35 students of class X F. The data collected through pre- and post-test, students’ questionnaires, observation notes and interviews. The data were analyzed descriptively. The result found that after using problem based learning, the students’ cognitive result percentage increased, from 1st cycle 51% to 2nd cycle 60% and 3rd cycle is 86%. Based on the questionnaire data, 49% of students strongly agree that the problem based learning model can help in learning biotechnology. The improvement of percentages cognitive result show the higher number of students complete the material increased in each cycle